An Analysis of Word Formation Processes in Selected Articles in Gontor Magazine and Their Relevance To ELT Writing Instruction - Anggun Rakhmalia; Eka Indah Nuraini; Diska Fatima Virgiyanti; Dinar Dipta; Aries Fachriza (English Teaching Journal : A Journal of English Literature, Language and Education, 2026)
This study aims to identify various types of word-formation processes and their frequencies in English-language articles published in the Gontor magazine, and to explore their relevance to the teaching of writing skills in the context of English Language Teaching (ELT). The background of this study was the urgency of understanding word formation to enrich vocabulary mastery and morphological awareness among learners, particularly in Islamic educational settings. Such understanding significantly contributed to the development of writing skills through precise word choice, lexical diversity, and the composition of more accurate, formal, and coherent texts. The research adopted qualitative approach, particularly content analysis. Primary data consisting of word-formation processes were obtained from ten English articles in Gontor magazine. The data were then analyzed through stages of identification, classification, and description by applying Krippendorff’s content analysis theory and Yule’s classification of word formation. Frequency calculations were also employed to determine the most requently occuring processes. The findings identified five types of word formation processes with a total of 269 occurrences: derivation (69, 5%), borrowing (16, 3%), compounding (13, 01%), initialism (0, 7%), and multiple processes (0, 3%). Among these, derivation appeared as the most dominant type. The results indicated that understanding word formation contributes to vocabulary development and enhances writing quality through more organized and varied linguistic patterns. In addition, the dominance of formal linguistic forms and the absence of processes, such as coinage and blending, suggest that articles in Gontor magazine consistently employ an academic writing style. Therefore, the magaize can serve as a relevant teaching source for writing instruction in ELT, particularly within the context of Islamic education.